The first Hochschild cohomology group of a schurian cluster-tilted algebra - Assem, Ibrahim (2009)
Given a cluster-tilted algebra B we study its first Hochschild cohomology group HH1(B) with coefficients in the B-B-bimodule B. We find several consequences when B is representation-finite, and also in the case where B is cluster-tilted of type Ã.